MicroRNA-4443 Causes CD4+ T Cells Dysfunction by Targeting TNFR-Associated Factor 4 in Graves’ Disease - Qi, Yicheng; Zhou, Yulin; Chen, Xinxin; Ye, Lei; Zhang, Qianwei; Huang, Fengjiao; Cui, Bin; Lin, Dongping; Ning, Guang; Wang, Weiqing; Wang, Shu (Frontiers in Immunology, 2017)
Context: Aberrant CD4+ T cell function plays a critical role in the process of Graves' disease (GD). MicroRNAs (miRNAs) are important regulators of T cell activation, proliferation and cytokine production. However, the contribution of miRNAs to CD4+T cell dysfunction in GD remains unclear. Objective: To investigate how certain miRNA causes aberrant CD4+ T cell function in GD patients. Methods: We compared the expression pattern of miRNAs in CD4+ T cells from untreated GD patients with those from healthy controls. The most significantly dysregulated miRNAs were selected and their correlations with clinical parameters were analyzed. The effect of miR-4443 on CD4+ T cells cytokines production and proliferation was assessed. The potential gene target was identified and validated. Results: GD patients had unique pattern of miRNA expression profile in CD4+ T cells comparing to healthy subjects. MiR-10a, miR-125b and miR-4443 were the three most significantly dysregulated miRNAs. The elevated miR-4443 levels were strongly correlated with clinical parameters in an independent dataset of untreated GD patients (N=40) while miR-4443 was normally expressed in GD patients with euthyroidism and negative TRAb level. We found that miR-4443 directly inhibited TNFR-associated factor (TRAF) 4 expression to increase CD4+ T cells cytokines secretion as well as proliferation through the NF-κΒ pathway. Furthermore, the TRAF4 levels in GD patients were inversely correlated with miR-4443, and knocking down TRAF4 had a similar effect with miR-4443 overexpression. Conclusion: The increased expression of miR-4443 induced CD4+ T cells dysfunction by targeting TRAF4, which may cause Graves’ diseases.